Ursodeoxycholic Acid Influences the Expression of p27(kip1) but Not FoxO1 in Patients with Non-Cirrhotic Primary Biliary Cirrhosis - Milkiewicz, Malgorzata (Hindawi Publishing Corporation, 2014)
Background. Enhanced expression of cell cycle inhibitor p27(kip1) suppresses cell proliferation. Ursodeoxycholic acid (UDCA) delays progression of primary biliary cirrhosis (PBC) but its effect on p27(kip1) expression is uncertain. Aims. To analyze the expression of p27(kip1) and its transcription modulator FoxO1 in patients with PBC, and to assess the impact of UDCA on this pathway. Materials and Methods. The examined human tissue included explanted livers from patients with cirrhotic PBC (n = 23), primary sclerosing cholangitis (PSC; n = 9), alcoholic liver disease (ALD; n = 9), and routine liver biopsies from patients with non-cirrhotic PBC (n = 26). Healthy liver samples served as controls (n = 19). Livers of FoxO-deficient mice were also studied. mRNA and protein expressions were analyzed by real-time PCR and Western blot. Results. p27(kip1) expression was increased in cirrhotic and non-cirrhotic PBC. FoxO1 mRNA levels were increased in PBC (8.5-fold increase versus controls). FoxO1 protein expression in PBC was comparable to controls, but it was decreased in patients with PSC and ALD (63% and 70% reduction, respectively; both P < 0.05 versus control). UDCA-treated non-cirrhotic patients with PBC showed decreased expression of p27(kip1) mRNA. Conclusion. PBC progression is characterized by a FoxO1-independent increase of p27(kip1) expression. In early PBC, UDCA may enhance liver regeneration via p27(kip1)-dependent mechanism.